1001 great ideas for teaching & raising children with autism or Asperger's - Notbohm, Ellen (Future Horizons, Inc., 2010)
Contains 1001 suggestions for meeting the challenges faced by children with autism spectrum disorders, covering sensory integration, communication, language, daily living, social issues, behavior, and education.